Complexity calculation of coding and information security system based on threshold secret sharing scheme used for electronic voting - Larisa V. Cherkesova; Olga A. Safaryan; Alexander V. Mazurenko; Nadezhda S. Arkhangelskaya (Advanced Engineering Research)
Introduction . One of the tasks arising in cryptography is to ensure the safe and honest conduct of e-voting. This procedure provides that voters submit their votes electronically - for example, through electronic terminals. A new algorithm for the distribution of threshold sensitive data for electronic voting is proposed. Materials and Methods . The results are obtained on the basis of the following methodology: finite field theory, theory of algorithms, projective geometry, and linear algebra. The developed cryptosystem is based on the application of geometric objects from projective geometry which makes it possible to use the apparatus of linear algebra to make effective decisions on cryptographic problems. To estimate the complexity of the described algorithms, classical results from the theory of algorithms are applied. Research Results . This paper describes the cryptographic algorithms of secret sharing and its subsequent restoration based on special structural properties of projective spaces over finite fields, and their link with Galois fields of the appropriate order. The component parts of these algorithms, specifically, the construction of injective mapping from a residue ring prime modulo into the projective space over finite field of specific dimension; the generation of secret shares and secret; the procedure of secret sharing and its restoration, are described in great detail. The algorithmic time complexity calculations of the formal algorithms are given. Discussion and Conclusions . The described scheme is useful for electronic voting and in other spheres where methods of threshold cryptography are applied.